Er:YAG Laser Versus Conventional Surface Treatment of Lithium Disilicate: In Vitro Study: Er:YAG Laser as surface treatment in lithium disilicate - Poquioma Choque, Cesar Manuel; Calle-Chavez, Rodolfo; Hinojosa Pedraza, Fabricio; Atoche-Socola, Katherine Joselyn (Journal of Lasers in Medical Sciences, 2025)
Introduction: The high-power 2940 nm Er:YAG (erbium-doped yttrium aluminium garnet) laser increases the rough surface of lithium disilicate, increasing the bonding strength of ceramics when they are bonded to the tooth using resin matrix cement. This investigation aimed to compare the Er:YAG laser with the conventional surface treatment of lithium disilicate. Methods: In this study, 50 lithium disilicate discs (5 mm diameter×2 mm thickness) were divided into five groups (n=10): Control group (CG) (10% hydrofluoric acid followed by 37% phosphoric acid), Group 1 (G1) (ER:YAG laser energy of 300 mJ/50 µs), Group 2 (G2) (Er:YAG laser energy of 400 mJ/50 µs), Group 3 (G3) (Er:YAG laser energy of 500 mJ/50 µs), and Group 4 (G4) (10% hydrofluoric acid, Er:YAG laser energy of 500 mJ/50 µs). After completing the surface treatments, 6 mm high Tygon was fixed and filled with self-adhesive dual resin cement (SET PP SDI Limited, Victoria, Australia). The samples were stored for 24 hours and subjected to shear tests until structural failure. Results: ANOVA analysis found no statistically significant difference between the groups analyzed (P=0.0689). G2 had the highest bond strength with 12.6±3.2 MPa, while G1 had the lowest with 9.5±2.2 MPa, followed by the CG 9.8±3.2. It was observed that with higher laser irradiation power, the adhesive strength decreased, as evidenced in G3 with 11.6±1.9 MPa. Conclusion: The radiation power of 400 mJ, frequency of 20 Hz, and pulse duration of 50 µs improved the bond strength between lithium disilicate and dual resin cement. However, the group that obtained the lowest strength was Group 3, with a laser energy of 500 mJ/50 µs, generating highly expulsive zones in lithium disilicate.